Engendering leadership in the Indian workplace – a framework on cross-level linkages. (2nd October 2017) - Chakravarty, Arjya; Bhatnagar, Jyotsna
Abstract : Purpose: Gender inequality is a critical economic challenge. A need to conceptualize and understand gender-based issues is of utmost importance to frame policies and processes for healthy workplaces. The paper aims to discuss these issues. Design/methodology/approach: This study attempts to capture the nuances of "gender diversity" issues at the Indian workplace from a grounded theory perspective by highlighting the viewpoints of women leaders and their organizations in the Indian context. Findings: The findings reveal certain important themes. Indian organizations which have eliminated stereotyping and sex typing (stereotypical categorization of people according to conventional perceptions of sex) in roles and have implemented gender neutral policies and processes have become preferred employers and achieved better business results. Research limitations/implications: The study has proposed a linkage framework (Figure 1 ) and has suggested ways to understand an organization's gender imbalance and lack of gender leadership with factors in the micro and macro environment. Organizations may use this model to gain perspective and adapt and invent policies and processes to have more gender diversity at workplace, for sustainable business results. Organizations should deepen their understanding of how "engendering leadership" should be embedded into the macro, micro and meso levels of an organization. Practical implications: Organizations that have created gender neutralism by procreating a performance and talent-driven culture find themselves creating positive business results. This was made possible by involving all stakeholders in the efforts to remove and negate gender myths and biases. A false sense of complacency, by creating rules and policies which were never implemented in spirit, proved to be detrimental. Social implications: This research attempts to investigate gender diversity's coherence with the other features of the broader social context. Originality/value: To gain perspective of how this phenomenon is manifested in reality in the Indian organizations, the authors conducted a qualitative study to gain deep immersed insights. This research has attempted to contribute and enrich the literature on gender leadership using a grounded theory approach. None of the earlier gender-related studies have applied grounded theory as a methodology.